2008
DOI: 10.2337/db07-0484
|View full text |Cite
|
Sign up to set email alerts
|

Association of the ATP-Binding Cassette Transporter A1 R230C Variant With Early-Onset Type 2 Diabetes in a Mexican Population

Abstract: OBJECTIVE—The ATP-binding cassette transporter A1 (ABCA1) R230C variant is associated with low HDL cholesterol levels, obesity, and the metabolic syndrome in Mexican-Mestizos. Because a pivotal role for ABCA1 in pancreatic β-cell function was recently observed in the mouse model, we assessed the association of this variant with type 2 diabetes in this population. RESEARCH DESIGN AND METHODS—The initial group included 446 unrelated Mexican individuals: 244 with type 2 diabetes aged 20–69 years (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 26 publications
6
70
0
1
Order By: Relevance
“…This notion is also supported by studies in humans displaying altered HDL metabolism due to polymorphisms in the ApoA-I and ABCA1 genes that have been associated with increased risk of diabetes and impaired glucose uptake (Morcillo et al 2005;Villarreal-Molina et al 2008). Heterozygotes for rare mutations in the ABCA1 gene that profoundly decrease HDL-C levels were found to be less glucose tolerant than their unaffected relatives (Vergeer et al 2010).…”
Section: Hdl Metabolism Subclasses and Catabolismsupporting
confidence: 60%
“…This notion is also supported by studies in humans displaying altered HDL metabolism due to polymorphisms in the ApoA-I and ABCA1 genes that have been associated with increased risk of diabetes and impaired glucose uptake (Morcillo et al 2005;Villarreal-Molina et al 2008). Heterozygotes for rare mutations in the ABCA1 gene that profoundly decrease HDL-C levels were found to be less glucose tolerant than their unaffected relatives (Vergeer et al 2010).…”
Section: Hdl Metabolism Subclasses and Catabolismsupporting
confidence: 60%
“…Subjects carrying loss-of-function mutations in ABCA1 show impaired insulin secretion but not insulin resistance 34,35 . In our present study, a significant association was identified between polymorphisms within ABCA1 SNP 22 found that the ABCA1 R230C variant is associated with early-onset T2DM in the Mexican population. The maximum allele frequency of the R230C variant however is less than 5% for the population in our study.…”
Section: Discussionmentioning
confidence: 66%
“…All the selected SNPs were selected in previous studies and exhibit allele frequencies of more than 5% in the Han Chinese population 22,24 . Linkage disequilibrium (LD) was performed with HAPLOVIEW 4.1, and the result showed LD between rs2487039 and rs2230806 (r 2 = 0.97).…”
Section: Snp Selection and Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…DM in older adults can be treated in a timely manner and even prevented in people who present certain polymorphisms that cause the development of diabetes mellitus by themselves or that are at risk factor for their development, such as the rs13266634 of the gene SLC30A8 or SNP rs64771077 from JMJD1C gene, which are by diabetes a protector factor. [39][40][41] …”
Section: Resultsmentioning
confidence: 99%